DESIGN AND IMPLEMENTATION OF COMPUTER AIDED SYSTEM FOR QUALITY IMPROVEMENT INSPECTION AND TESTING FOR BOILER IN THERMAL ELECTRIC POWER STATION (Journal of Engineering, 2007)
There is a problem, in Iraq, due to the multitude of malfunction after the overall annual maintenance has been achieved, and that raises the cost of continuous repairs, one of the reasons of this problem, is the absence of planned testing and automation for testing devices, the second reason is the neglect of concentrating on a database, the third one is not following an integrated testing system for all parts, as well as, there are no documented reports for inspected parts. Most of various nondestructive inspection techniques have been achieved random selection steps. The lack of a documentation system leads to lack of historical information a bout failures parts of a boiler that affect inspection decision process. This paper summarizes Programmed system designing and computerized for internal inspection of boiler heatsurfaces (IIBHS) at Nassyriah power station as an example.